Party Fragmentation, the Proportional System and Democracy in Slovenia. (November 2022) - Fink-Hafner, Danica; Novak, Meta
In Slovenia, political parties have been the key actors in opting for a proportional electoral system and constitutional choice of a parliamentary system, both of which are believed to help to develop a consensual type of democracy. However, a vicious circle involving a fragmented party system and a proportional electoral system has not only led to polarisation within the party system, but has also contributed to problems of democratic governability and legitimacy. The destabilisation of the party system since 2011 has not only caused a crisis of political legitimacy and accountability, but has also contributed to a recent trend of de-democratisation. At the moment, there does not appear to be a realistic alternative to the existing electoral rules in the near future, in spite of recurring calls by an anti-communist party (Slovenian Democratic Party) to introduce a majoritarian system.